Three‐Dimensional Electrical Structure Beneath the Epicenter Zone and Seismogenic Setting of the 1976 Ms7.8 Tangshan Earthquake, China - Cai, Juntao; Chen, Xiaobin; Dong, Zeyi; Zhan, Yan; Liu, Zhongyin; Cui, Tengfa; Jiang, Feng (Geophysical research letters, 2023)
Based on magnetotelluric array data and the three‐dimensional (3D) inversion algorithm, we obtain the 3D electrical structure of the 1976 Ms7.8 Tangshan earthquake zone. The seismogenic structure comprised a thick resistive anomaly located east of the Tangshan fault (TSF), a thin resistive belt extending westward, and the TSF zone. A geodynamic model is proposed based on the 3D electrical model and the other research findings. The model indicates that the primary cause of the Tangshan earthquake was the almost EW‐trending horizontal pushing from the west. The local uplift of deep thermal materials on the west side of TSF produces tensile deformation superimposed on the existing shear deformation. The combined effect of these two forces controls the Tangshan earthquake deformation characteristic. Prevailing horizontal pushing from the west and local uplift of hot material may be associated with the Tibet Plateau's eastward escape and the subduction of the Pacific plate. Plain Language Summary The 1976 Ms7.8 Tangshan earthquake was the greatest in eastern China during the past 300 years, and it was an unusual event that occurred immediately beneath the city. It has caused significant economic and human losses. Even though previous Seismologists have conducted various related studies, there are still several controversies about the Tangshan earthquake's seismogenic structure and driving mechanism. An accurate structure model is required to resolve these problems. The magnetotelluric array data and the 3D inversion technology with topography were used to create a reliable 3D electrical model of the Tangshan earthquake zone. The model demonstrates that the seismogenic structure comprised a thick resistive anomaly located east of the source region, a thin resistive belt extending westward, and the Tangshan fault zone. The horizontal pushing force from the west and local thermal material uplift produced the Tangshan earthquake. Prevailing horizontal pushing from the west and local uplift may be associated with the Tibet Plateau's eastward escape and the subduction of the Pacific plate. The research findings not only improve our understanding of the mechanism of typical strike‐slip and extensional large earthquakes in North China but also provide a scientific basis for predicting comparable destructive strong earthquakes. Key Points Detailed three‐dimensional crustal structure beneath the Ms7.8 Tangshan earthquake zone is obtained The seismotectonics comprised a resistive anomaly located east of the Tangshan fault (TSF), a resistive belt extending westward and the TSF The Tangshan earthquake was triggered by the prevailing horizontal pushing force from the west and the local uplift of hot material